The distribution of glacial meltwater in the Amundsen Sea, Antarctica, revealed by dissolved helium and neon. Issue 3 (12th March 2016) - Kim, Intae; Hahm, Doshik; Rhee, Tae Siek; Kim, Tae Wan; Kim, Chang‐Sin; Lee, SangHoon
Abstract: The light noble gases, helium (He) and neon (Ne), dissolved in seawater, can be useful tracers of freshwater input from glacial melting because the dissolution of air bubbles trapped in glacial ice results in an approximately tenfold supersaturation. Using He and Ne measurements, we determined, for the first time, the distribution of glacial meltwater (GMW) within the water columns of the Dotson Trough (DT) and in front of the Dotson and Getz Ice Shelves (DIS and GIS, respectively) in the western Amundsen Sea, Antarctica, in the austral summers of 2011 and 2012. The measured saturation anomalies of He and Ne (ΔHe and ΔNe) were in the range of 3–35% and 2–12%, respectively, indicating a significant presence of GMW. Throughout the DT, the highest values of ΔHe (21%) were observed at depths of 400–500 m, corresponding to the layer between the incoming warm Circumpolar Deep Water and the overlying Winter Water. The high ΔHe (and ΔNe) area extended outside of the shelf break, suggesting that GMW is transported more than 300 km offshore. The ΔHe was substantially higher in front of the DIS than the GIS, and the highest ΔHe (31%) was observed in the western part of the DIS, where concentrated outflow from the shelf to the offshore was observed. In 2012, the calculated GMW fraction in seawater based on excess He and Ne decreased by 30–40% compared with that in 2011 in both ice shelves, indicating strong temporal variability in glacial melting. Key Points: Large excess of He and Ne, attributable to glacial melting, were observed in the Amundsen Sea Glacial meltwater is transported over 300 km offshore in the Amundsen Sea Strong temporal variation of glacial meltwater was observed between 2011 and 2012